Forage yield and morphological composition of native maize under semi-arid conditions - Godina Rodríguez, Juan Eduardo; Garay Martínez, Jonathan Raúl; Mendoza Pedroza, Sergio Iban; Joaquín Cancino, Santiago; Rocandio Rodríguez, Mario (Revista Mexicana de Ciencias Agrícolas, 2020)
Environmental conditions in semi-arid areas limit the productivity of forage species used in animal feed; however, corn (Zea mays L.) has a wide adaptation to different environmental conditions of temperature, precipitation, altitude, soil, among others. The objective of the present study was to evaluate the yield and morphological composition of ten native corn genotypes, a hybrid and a synthetic variety, during the cycle Spring-Summer 2017. A randomized complete block experimental design was used, and an analysis of variance was performed; the means of the treatments were compared with the Tukey test. The variables evaluated were: yield of total dry matter (TDM), and by morphological component: leaf (lDM), stem (sDM), ear (eDM), panicle (pDM) and dead matter (dmDM), plant height (PH), number of leaves (NL), leaf length (LL), leaf width (LW) and the leaf/stem ratio (L/S). The highest and lowest TDM yield was obtained by the Raton×Tuxpeño Norteño genotype and the A6-069-B hybrid, with 8 888 and 3 113 kg DM ha-1, respectively. The highest height (180 cm) was obtained by the genotypes Raton×Tuxpeño Norteño and Olotillo×Tuxpeño. The largest number of leaves number was presented by the genotype Tuxpeño Norteño×Olotillo with 11.6. The largest leaf:stem ratio (2.1) was in the synthetic variety Breve Padilla. More research is needed on the improvement by recurrent selection of the Raton×Tuxpeño Norteño genotype to obtain a higher yield and nutritional value in corn fodder.